Mechanical loading‐induced alveolar bone remodeling is suppressed in the diabetic state via the impairment of the specificity protein 1/vascular endothelial growth factor (SP1/VEGF) axis - Rina Hoshino; Nobuhisa Nakamura; Taisuke Yamauchi; Yuki Aoki; Megumi Miyabe; Sachiko Sasajima; Reina Ozaki; Takeo Sekiya; Takuma Sato; Masako Tabuchi; Ken Miyazawa; Keiko Naruse (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction Orthodontic treatment involves alveolar bone remodeling in response to mechanical loading, resulting in tooth movement through traction‐side bone formation and compression‐side bone resorption. However, there are conflicting reports regarding alveolar bone resorption during the orthodontic treatment of patients with diabetes. Materials and Methods Diabetes was induced in 8‐week‐old C56BL/6J mice using streptozotocin (STZ). Four weeks after the injection of STZ, a mechanical load was applied between the first and second molars on the right side of the upper jaw using the Waldo method with orthodontic elastics in diabetic (DM) and normal (N) mice tooth movement, gene expression, osteoclast counts, alveolar bone residual volume, and bone beam structure were evaluated. Results The duration until spontaneous elastic loss was significantly longer in the DM group, suggesting that tooth movement may be inhibited in the diabetic state. The number of osteoclasts at 7 days after mechanical loading and the alveolar bone resorption were both significantly lower in the DM group. The gene expression levels of vascular endothelial growth factor (VEGF), a protein related to alveolar bone remodeling, and specificity protein 1 (SP1), a transcription factor of the VEGF gene, were significantly lower in the DM group than in the N group on the compression side of mechanical loading. Conclusions Mechanical loading‐induced alveolar bone remodeling is suppressed in the diabetic state. Our results suggest that VEGF is a key molecule involved in impaired bone remodeling under mechanical loading in the diabetic state.